(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
River or stream discharge is of great importance ranging from flood control, power generation, irrigation, water supply and dam construction. Hence, the need for stream discharge measurement becomes a paramount importance in water resources evaluation. A comparison has been made between stream discharge values using the Weir, Current metre and Float methods in Malmo tributary which is found in the northernmost part of River Kubanni in Zaria. This was made in order to establish the most effective method for measuring stream discharge for small rivers. The result observed from this study shows that there is no significant difference between the river discharges from the three techniques. This means that the techniques were suitable for the stream discharge measurements on the stream channel. However, the field observation shows that the weir technique is of greater applicability and more advantageous for continuous discharge measurements than the current metre and float methods. The weir technique can be used throughout the year and when the river becomes too shallow for current metre to be used. Also, the weir is of greater advantage compared to the float method, because the float is sometimes affected by vegetal growth, eddy current and wind. It is therefore recommended that for small river channels, the weir method is the most effective technique for stream discharge measurement